Households, Financial Distress, and Predatory Lending: An Experimental Study - Irwan Trinugroho; Ariyanto Adhi Nugroho; Harmadi Harmadi; Joko Suyono; Muh Juan Suam Toro (University of Merdeka Malang, 2017)
A substantial part of households and micro enterprises, particularly in developing countries including Indonesia, did not have access to formal financial institutions which then lead them to borrow money from illegal loan providers. Using an experimental study, we tested whether predatory loan, an illegal short-term loan with high-interest rate, was preferable or not by comparing with pawnshop loan, bank loan and household’s limited saving when households confront with financial distress. We divided the participants into three groups: lower low, low, and upper low income. We found that predatory loan was preferable especially for the lower low and low-income group. Result also confirmed that even if the predatory loan charge was increased, the lower low- and low-income groups still prefer to ease their financial distress through predatory loans. Moreover, the longer the duration of the predatory loan, the higher its probability to be chosen as a funding source in times of household financial distress.DOI: https://doi.org/10.26905/jkdp.v21i3.1261